What Determines Budget Absorption in Local Government? Evidence from Aceh Province, Indonesia - Amellya, Shebrina; Jalaluddin, Jalaluddin; Batara, Gamal (Journal of Accounting Research, Organization and Economics, 2023)
Objective This research aims to examine the factors affecting budget absorption in a local government taking the context of Aceh Province, Indonesia, which consistently falls below 100 percent from 2018 to 2020. This indicates that the level of budget absorption has not yet reached the targeted achievement, highlighting the need to investigate factors affecting effective utilization of allocated funds within Aceh province.Design/Methodology We use a group analysis unit consisted of 23 districts/cities in Aceh Province and collect data from 2018 to 2020. This research uses a time horizon, in panel data form, which is a combination of time series and cross section data. We use census method where the entire study population is observed. We collect data from secondary data sources; Indonesia Central Agency on Statistics (BPS), local government financial reports (LKPD), and local government budget (APBD).Results The result shows that the remaining budget for of previous year, the size of the local government, and the timing of budgeting had an effect on budget absorption in district/city governments in Aceh Province. Thus, it is very important for local government to control these variables in order to increase the absorption level of the budget.Research limitations/implications The findings of this study have important implications for government, as they suggest that government should control the influencing variables, especially the remaining budget of the previous year and the budgeting timing, in order to increase the absorption level of the budget.Novelty/Originality This study uses census method where the entire study population is observed. Previous studies used samples to represent study population.